Acute transverse myelitis progressing to spinal cord atrophy. a case report - Abdul Aziz, Azian (2021)
Acute transverse myelitis (ATM), an inflammatory demyelinating myelopathy, usually presents with lower limb weakness, back pain, and sphincter disturbances in childhood. Magnetic resonance imaging (MRI) commonly shows enlargement and increased signal intensity of the spinal cord in a T2-weighted image. The clinical sequalae of ATM includes complete paraplegia, and when spinal cord atrophy appears during the disease course, the outcome becomes unfavourable. There have been only a few case reports on spinal cord atrophy following ATM in children. We report a case of a 9 year old girl in which spinal cord atrophy developed following acute transverse myelitis and no motor recovery occurred despite of appropriate treatment instituted in a timely manner.